2019
DOI: 10.5334/gjgl.620
|View full text |Cite
|
Sign up to set email alerts
|

Associating the origin and spread of sound change using agent-based modelling applied to /s/-retraction in English

Abstract: The study explored whether an asymmetric phonetic overlap between speech sounds could be turned into sound change through propagation around a community of speakers. The focus was on the change of /s/ to /ʃ/ which is known to be more likely than a change in the other direction both synchronically and diachronically. An agent-based model was used to test the prediction that communication between agents would advance /s/-retraction in /str/ clusters (e.g. string). There was one agent per speaker and the probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…The most well-studied /ɹ/-conditioned sound change is the retraction of /s/ in /stɹ/ clusters (e.g., street pronounced as [ʃtɹit]). It is unclear what the primary initiating factor of /str/ retraction was, but it is either directly or indirectly triggered by the following /ɹ/, and appears as a pronunciation variant in many English-speaking communities, such as Pennsylvania (Labov 1984;Gylfadottir 2015), Georgia (Phillips 2001), Louisiana ( Rutter 2011), North Carolina (Piergallini 2011;Wilbanks 2017), Oklahoma (Rutter 2014), Newfoundland (Clarke 2008), the UK (Altendorf 2003;Bass 2009;Glain 2014), New Zealand (Lawrence 2000;Bauer & Warren 2008;Gordon & Maclagan 2008), and Australia (Stevens & Harrington 2016;Stevens et al 2019). Two different mechanisms underlying /stɹ/ retraction have been postulated.…”
Section: Sound Changes Involving /ɹ/mentioning
confidence: 99%
See 1 more Smart Citation
“…The most well-studied /ɹ/-conditioned sound change is the retraction of /s/ in /stɹ/ clusters (e.g., street pronounced as [ʃtɹit]). It is unclear what the primary initiating factor of /str/ retraction was, but it is either directly or indirectly triggered by the following /ɹ/, and appears as a pronunciation variant in many English-speaking communities, such as Pennsylvania (Labov 1984;Gylfadottir 2015), Georgia (Phillips 2001), Louisiana ( Rutter 2011), North Carolina (Piergallini 2011;Wilbanks 2017), Oklahoma (Rutter 2014), Newfoundland (Clarke 2008), the UK (Altendorf 2003;Bass 2009;Glain 2014), New Zealand (Lawrence 2000;Bauer & Warren 2008;Gordon & Maclagan 2008), and Australia (Stevens & Harrington 2016;Stevens et al 2019). Two different mechanisms underlying /stɹ/ retraction have been postulated.…”
Section: Sound Changes Involving /ɹ/mentioning
confidence: 99%
“…4 Previous research such as Baker et al (2011) leads us to expect patterns like /stɹ/ retraction and /tɹ/ and /dɹ/ affrication to be instances of phonological assimilation for most talkers, and thus be less sensitive to the phonetic details of the local triggering /ɹ/ than during the initial stages of these changes. In other words, these talkers have performed the reclassification of /s/ before /tɹ/ into the /ʃ/ category, as modeled by Stevens et al (2019). While /ɹ/ may continue to exert some influence on the preceding sound, it is not the same process as that which conditioned the initial change, especially if the target sound is now phonologically distinct.…”
Section: Sound Changes Involving /ɹ/mentioning
confidence: 99%
“…Our study thus shows that there may be systematicity at a different level than typically considered by linguists, and that naïve language users are sensitive to patterns at this particular level (see also Stevens, Harrington, & Schiel, 2019) even though there is no clear form-function relationship.…”
Section: Discussionmentioning
confidence: 65%
“…Although there are many remaining questions to ask about the nature of this relationship, this observation has implications for our understanding of the sound change. For example, Stevens et al (2019:11) suggested that an individual's split of /stɹ/ from /s/ (e.g., an intermediate /stɹ/ form), or merger of /stɹ/ with /ʃ/, is more likely to occur if speakers have more proximal /s/-/ʃ/ in acoustic space (as is the case for our working-class speakers). Therefore, the distributions of the rest of the sibilant space are relevant for examinations of /stɹ/ retraction across communities and social groups within communities.…”
Section: Discussionmentioning
confidence: 83%
“…Beyond this work, however, it is unclear whether a paucity of research on =ʃ= variation is because speakers do not make as much use of it for socioindexical meaning, because it is relatively stable over time, or, more simply, because of an omission on the part of researchers to fully investigate these issues. For example, the sound-change literature observes that change in voiceless sibilants is asymmetrical such that =s= retracts to(ward) =ʃ=, but that =ʃ= does not appear to front to(ward) =s= (Stevens, Harrington, & Schiel, 2019). There are no claims in sociolinguistics that =ʃ= is used for the same type of identity work as =s=, though of course this may be due simply to the absence of research examining =ʃ= variation in the first place.…”
Section: Variation In =ʃ=mentioning
confidence: 99%